CTBP1 and CTBP2 mutations underpinning neurological disorders: a systematic review (2022)
ABSTRACT: Abstract C-terminal binding proteins (CtBP1/2) are transcriptional coregulators that play a signifcant role during vertebrate neu rodevelopment. This systematic review aims to identify case reports with genetic variants in CTBP1 and CTBP2 associated with brain development syndromes. We screened diferent databases (PubMed, Scopus, Google Scholar, LILACS) by systematically searching journals and checking reference lists and citations of background papers. We found fourteen cases (10 males) from fve papers carry ing two pathogenic, heterozygous variants in the CTBP1 gene (13 individuals carried the missense mutation c.991C T, p.Arg342Trp, and one subject carrying the 2-base pair deletion c.1315_1316delCA, p.Gln439ValfsTer84). These mutations were de novo in 13 cases and one case of maternal germinal mosaicism. Two variants are in the same domain of the protein: Pro-Leu-Asp-Leu-Ser (PLDLS) C terminal. Patients with these mutations exhibit a phenotype with intellectual disability, HADDTS syndrome (hypotonia, ataxia, developmental delay, and tooth enamel defects), and cerebellar volume loss. We did not identify reported cases associated with homozygous mutations harbored in CTBP1. We did not identify any report of neurodevelopment phenotypes associated with heterozygous or homozygous CTBP2 mutations. Due to CTBP2/RIBEYE being a gene with dual function, identifying and interpreting the potential pathogenic variants is challenging. Further, homozygous mutations in the CTBP2 gene may be lethal. The mechanisms involved in the pathogenesis of neu rodevelopment due to variants of these proteins have not yet been elucidated, despite some functional evidence. Further studies should be conducted to understand these transcription factors and their interaction with each other and their partners.